Inhibition of sphingolipid metabolism in osteosarcoma protects against CD151-mediated tumorigenicity - Hongsheng Wang; Xinmeng Jin; Yangfeng Zhang; Zhuoying Wang; Tao Zhang; Jing Xu; Jiakang Shen; Pengfei Zan; Mengxiong Sun; Chongren Wang; Yingqi Hua; Xiaojun Ma; et al. (figshare, 2022)
Abstract Osteosarcoma is the most common primary bone tumor, with a poor prognosis owing to the lack of efficient molecular-based targeted therapies. Previous studies have suggested an association between CD151 and distinct consequences in osteosarcoma tumorigenicity. However, the potential of CD151 as a therapeutic target has not yet been sufficiently explored. Here, we performed integrated transcriptomic and metabolomic analyses of osteosarcoma and identified sphingolipid metabolism as the top CD151-regulated pathway. CD151 regulates sphingolipid metabolism primarily through SPTCL1, the first rate-limiting enzyme in sphingolipid biosynthesis. Mechanistically, depletion of CD151 enhanced c-myc polyubiquitination and subsequent degradation. c-myc is vital for the transcriptional activation of SPTLC1. Functionally, sphingolipid synthesis and the SPTLC1 inhibitor, myriocin, significantly suppressed the clonogenic growth of CD151-overexpression cells. Importantly, myriocin selectively restrained CD151-high expression tumor growth in preclinical patient-derived xenograft models. Collectively, these data establish that CD151 is a key mediator of sphingolipid metabolism and provide a new approach to developing novel CD151-based targeted therapies for osteosarcoma.
Keywords: Biochemistry; Cell Biology; Genetics; Physiology; Pharmacology; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Cancer; Hematology